Returning Merchandise: Registering a Consumer Complaint - Mary N. Harrison (EDIS)
Consumers return purchases for a variety of reasons. Sometimes they change their minds and do not want an item. Perhaps the purchase cant be used as planned, the color or fit is wrong or the product is defective. Many times there would be no need to return items if the customer shopped carefully and planned ahead. However, even the most efficient shopper will occasionally find it necessary to return a purchase for exchange or replacement. This document is Fact Sheet 5011, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Revised: June 2005.